Surgeons' workload assessment during indocyanine-assisted deep endometriosis surgery using the surgery task load index: The impact of the learning curve - Spagnolo, Emanuela; Cristóbal Quevedo, Ignacio; Gortázar de las Casas, Sara; López Carrasco, Ana; Carbonell López, Maria; Pascual Migueláñez, Isabel; Hernández Gutiérrez, Alicia (Frontiers in Surgery, 2022)
Objective: Assess the surgeons’ workload during deep endometriosis surgery after ureteral ICG Design: prospective, consecutive, comparative, single-center study Population: 41 patients enrolled to deep endometriosis surgery with ureteral ICG from January 2019 to July 2021 at La Paz University Hospital Methods: Patients were divided into 2 groups: patients operated during 2019, during the beginning of ureteral ICG, and patients operated during 2020-21. After surgery, the SURG-TLX form was completed by the surgeons. We evaluated whether a workload reduction occurred. Main Outcomes Measures: Surgeon’s workload was measured using the SURG-TLX form, obtaining the total workload and 6 different dimensions (distractions, temporal demands, task complexity, mental demands, situational stress and physical demands) Results: A significant positive correlation was found between surgical complexity and situational stress (p=0.04). Mental demands (p=0.021), physical demands (p=0.03), and total workload (p=0.025) were significantly lower in the 2020-2021 surgeries. The mental demand, physical demands, and total workload perceived by the surgeons in 2019 was higher (68 [39-72], 27 [11-46.5], 229 [163-240], respectively) than in 2020-21 (40 [9-63], 11.5 [0-32.8], 152 [133.3-213.8], respectively). Distractions appeared to be higher in the 2020-2021 surgeries (8.5 [0-27.8]) than in the 2019 surgeries (0 [0-7]; p=0.057). Conclusions: Ureter ICG instillation prior to DE surgery significantly reduces the mental and physical demands and total workload of the surgeons in DE surgeries. Distractions appear to increase as surgical stress decreases.